1975
DOI: 10.2307/3279120
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Changes in Ascaris suum Intestine after Mebendazole Treatment In vivo

Abstract: The effect of in vivo treatment with mebendazole on the ultrastructural morphology of Ascaris suum intestine was investigated. Pigs, infected with A. suum, were fed ad libitum a medicated food containing mebendazole at a concentration of 30 ppm. Control and treated animals were killed 6, 9, 15, and 24 hr after the onset of feeding. The parasites were quickly collected from the pig intestinal tract and prepared for ultrastructural and cytochemical examination. Absence of secretory granules in the terminal web, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1

Year Published

1975
1975
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(43 citation statements)
references
References 0 publications
2
39
1
Order By: Relevance
“…The reason for this may be that a portion of fenbendazole is also taken up orally. This observation is in line with results obtained by Borgers and De Nollin (1975) investigating mebendazole effects in Ascaris suum. However, the path of drug uptake can ultimately only be elucidated by autoradiography.…”
Section: Fenbendazolesupporting
confidence: 94%
“…The reason for this may be that a portion of fenbendazole is also taken up orally. This observation is in line with results obtained by Borgers and De Nollin (1975) investigating mebendazole effects in Ascaris suum. However, the path of drug uptake can ultimately only be elucidated by autoradiography.…”
Section: Fenbendazolesupporting
confidence: 94%
“…Mebendazole induces degenerative changes in the intestinal cells of parasitic worms after treatment of their hosts (Borgers and De Nollin, 1975).…”
Section: Survey Of the Literaturementioning
confidence: 99%
“…Over 40 years ago it was shown that tetramisole (Aceves et al, 1970) and pyrantel (Aubry et al, 1970) both act as nicotinic receptor agonists and elicit spastic muscle paralysis due to prolonged activation of the excitatory nicotinic acetylcholine receptors (nAChRs) on body wall muscle of nematodes. Voltage-clamp studies using A. suum body wall muscle cells have shown that morantel, pyrantel, and levamisole mimic the actions of acetylcholine, with the following order of potency: morantel=pyrantel>levamisole>acetylcholine (Harrow and Gration, 1985).…”
Section: Imidazothiazole: Levamisole and Tetrahydropyrimidines: Pyramentioning
confidence: 99%